Evolving therapies in the treatment of hepatocellular carcinoma - Hans Christian Spangenberg; Robert Thimme; Hubert E Blum (Biologics: Targets & Therapy, 2008)
Hans Christian Spangenberg, Robert Thimme, Hubert E BlumDepartment of Medicine II, University of Freiburg, D-79106 Freiburg, GermanyAbstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors worldwide. The major etiologies and risk factors for HCC development are well defined and some of the steps involved in hepatocarcinogenesis have been elucidated in recent years. Therapeutic options that can be applied in curative or palliative intention are available and are dependent on the HCC stage. The therapeutic options fall into five main categories: (1) surgical interventions, including tumor resection and liver transplantation, (2) percutaneous interventions, including ethanol injection and radiofrequency thermal ablation, (3) transarterial interventions, including embolization and chemoembolization, (4) radiation therapy, and (5) drugs as well as gene and immune therapies. Until recently, no therapy existed for patients with advanced HCC. In 2007 a multikinase inhibitor (sorafenib) showed for the first time a significant increase in overall survival in patients with advanced HCC. Furthermore, several other agents that target different factors of hepatocarcinogenesis (eg, epidermal growth factor, insulin-like growth factors, hepatocyte growth factor, vascular endothelial growth factor, fibroblast growth factor, platelet-derived growth factor, and the transforming growth factors-α and -β), have emerged and been tested in clinical trials. This review gives an overview of the current therapeutic strategies and their clinical impact.Keywords: hepatocellular carcinoma, targeted therapy, sorafenib, antiangiogenesis